A monastery in decline: St Radegund's Abbey - Parfitt, Keith (Current Archaeology, 2008)
Keywords: bradsole

St Radegund's Abbey: A Re-Assessment of the Abbey Church - Davis, M.C.J. (Archaeologia Cantiana, 2006)
Keywords: bradsole

Danger – Falling Masonry: Rebuilding the Ruins of St Radegund’s Abbey, Kent - Huitson, Toby (University of Kent, 2004)
Despite a relative abundance of extant material, both documentary and architectural, St Radegund's Abbey, Kent (1193-1536) has been neglected in recent years. Its historiography shows how post-medieval concepts of the abbey's history have been profoundly shaped by representational conventions in contemporary visual and documentary media. An examination of its recorded history reveals that the abbey was at the height of its powers and wealth in the thirteenth century and experienced subsequent decline, above all in the late fifteenth century. Its standing architecture is then described; although difficult to interpret, the essential elements of the monastic ground-plan can be recovered with some confidence. The recorded documentary history and architectural material are then correlated and approximate dates of construction established. Finally, we outline the likely appearance of the monastic church by the early sixteenth century.
Keywords: bradsole

The Library of St. Radegund's Abbey - Sweet, Alfred H. (The English Historical Review, 1938)
Keywords: bradsole

St. Radegund's Abbey, Dover - Winbolt, S.E. (Archaeologia Cantiana, 1931)
Keywords: bradsole

Houses of Premonstratensian canons: The abbey of Bradsole or St Radegund - Page, William (A History of the County of Kent, 1926)
Keywords: bradsole

On the Praemonstratensian Abbey of St. Radegund, Bradsole in Polton, near Dover - Hope, W.H. St John (Archaeologia Cantiana, 1882)
Keywords: bradsole